New records of species of the Polyonyx sinensis group (Crustacea: Decapoda: Anomura: Porcellanidae) from Japan, the Philippines, Singapore, and Malaysia, with descriptions of two new species - Osawa, Masayuki; Naruse, Tohru; Ng, Peter K. L. (Zootaxa, 2018)
Five species of the genus Polyonyx Stimpson, 1858 are reported from southern Japan, the Philippines, Singapore, and Peninsular Malaysia. All of them belong to the P. sinensis group, which is morphologically defined by having the dactyli of the ambulatory legs each with the dorsal claw being much smaller than the ventral claw. Two species are described as new to science, one each from Peninsular Malaysia and the Ryukyu Islands in Japan, and their affinities are discussed. Polyonyx boucheti Osawa, 2007, P. heok Osawa & Ng, 2016, and P. thai Werding, 2001, are also newly reported from southern Japan, the Philippines, and Singapore. A key to the Indo-West Pacific species of the P. sinensis group is provided.